Preexposure Prophylaxis for Mitigating Risk of HIV Transmission During HIV Cure–Related Clinical Trials With a Treatment Interruption - Lelièvre, Jean-Daniel (J Infect Dis, 2019)
Analytical treatment interruption performed during human immunodeficiency virus (HIV) cure–related clinical trials exposes sex partners of participants in these trials to a risk of HIV transmission. Preexposure prophylaxis (PrEP), which emerged in recent years as a key strategy for preventing HIV transmission, is often considered a useful tool to prevent this risk. This article supports offering PrEP to the stable sex partners of participants in these trials but also notes limitations that must be addressed. It concludes that PrEP cannot on its own eliminate the risk of secondary transmission in this context.